PENINGKATAN HIGH-SENSITIVE CARDIAC TROPONIN (HS-CTN) SETELAH LATIHAN INTENSITAS TINGGI YANG INTENSIF - Indira Vidiari J; Nila Wahyuni; I Putu Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2018)
ABSTRACTThe role of exercise as a strategy for prevention, management and therapy in cardiovascular disease has been well described, but in some studies, it has been suggested that there is an increase in biomarkers in cardiac damage or cardiac troponin (cTn) after intensive, high-intensity exercise in healthy individuals. Several studies have shown significant increases in cardiac troponins after different types of exercise. The latest meta-analysis, showing that high-sensitivity cardiac troponin (hs-cTn) increases in about 83% of individuals after long and intensive exercise. The current pathophysiology of hs-cTn is not well understood. Several hypotheses have been proposed, such as transmembrane leakage from cytoplasmic free cTnT and cTnI or decreased troponin clearance from plasma, both caused by overloading of free radicals, myocardial stretching, elevated core temperature, or alteration of pH. Further research is needed with a full prospective study to evaluate the underlying pathophysiology of enhancing high sentivity cardiac troponin (hs-cTn) is an effective strategy for preventing or limiting cardiac injury and sport exercise safe for heart.Keywords: cardiac Troponin (cTn), high sensitivity cardiac troponin (hs-cTn), high intensity intensive exercise